The role of consciousness-raising through critical reflection in teachers’ professional development: A sociocultural perspective - Saman Ebadi; Nouzar Gheisari (Cogent Education, 2016)
This study, framed within Vygotskyan sociocultural approaches to teacher education, aimed at reconceptualizing the thinking and subsequent recontextualizing of the classroom practice of a participating teacher. An Iranian English as a Foreign Language (EFL) teacher with pseudonym -Sara- was the participant of the study. Sara’s conceptions of teaching and classroom behavior were changed through awareness-raising of and critical reflection on her teaching behavior. This was done through replacing her everyday concepts by conducting three workshops and reflection on her follow-up classroom behavior videotaped by Sara herself. The results of the study showed that the participating teacher, over a process of struggle with her past experiences, gradually replaced her old classroom practice. The findings can be illuminating for policy-makers and material developers who are striving for finding a solution to classroom complex dilemmas. It can also be rewarding for teacher educators and teachers trying to change the classroom practice of in-service teachers.